Ray-optical prediction of radio-wave propagation characteristics in tunnel environments-Part 2 : analysis and measurements - Kouyoumjian, Robert G. (2009)
The uniform theory of diffraction (UTD) developed in Part 1 is used to predict narrow- and wide-band propagation characteristics in tunnels at 900- and 1800-MHz frequencies. Narrow-band propagation characteristics is shown in spatial domain and wide-band propagation in time domain. In empty straight-tunnel environments, propagation exhibits a break-point phenomenon and has very short time delay spread. In empty curved or branched tunnel environments, propagation suffers higher loss. Vehicles cause additional propagation loss and larger varying time delay spread in tunnels. The measured results have validated the accuracy of the theoretical model and provided important information on narrow-band and wide-band propagation characteristics in empty, branched and obstructed tunnels.